Upper-Middle-Class Community Preferences Toward Sharia Insurance Products in Tanjung Medan Village: A Qualitative Study - Muhammad Aldi; Khairina Tambunan; Tri Inda Fadhila Rahma (Jurnal Investasi Islam, 2026)
This study examines the preferences of the upper-middle-class community toward Sharia insurance products in Tanjung Medan Village. The observed phenomenon indicates that although the market potential for Sharia insurance continues to grow, public participation remains relatively low compared to conventional insurance. This research aims to identify the main factors influencing community preferences, including understanding of Sharia principles, trust in Islamic financial institutions, perceived benefits, and social influences. The study employed a qualitative approach using in-depth interviews, observation, and documentation with purposively selected informants. The findings reveal that most respondents appreciate the ethical values and risk-sharing concept of Sharia insurance. However, low financial literacy and limited promotional efforts remain the primary obstacles to increasing public participation. The study concludes that strengthening education, transparency, and public awareness regarding Sharia insurance is essential to enhance public trust and participation. Policy recommendations include implementing community-based awareness programs and fostering collaboration between Sharia insurance companies and local religious leaders to strengthen community engagement.